(untitled) (Global Journal of Medical Research, 2022)
The research featured the development of formulae and technology of obtaining biologically active additives for functional foods with potential anti-inflammatory activity using a substance containing zinc (microelement) and plant raw material as source of natural biologically active substances. The relevance of the study is comes from the need for more effective use of natural biologically active compounds, the need to expand the range of domestic dietary supplements, in particular, those recommended for the prevention of disorders of the prostate activity and erectile dysfunction, with natural ingredients and import substitution. On the basis of scientific data and the results of the conducted research, substance containing zinc and a promising plant raw material containing biologically active substances were selected; their safety and potential properties were assessed. The optimal ratio and dosage of active ingredients in the composition has been scientifically substantiated.